AAR550 - Design III / Faculty of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2023)
The course focuses on comparative concept formation based upon analysis of precedents and basic contextual appraisal and site exploration. Fundamental principles relating to function, form and space will also be emphasized while addressing design concepts, architectural functions and spatial organisation. Design Project will focus on small simple structure with integrated knowledge of environmental science and construction.